Diseño de un plan de mejora de calidad en el servicio para el restaurante Bambao ubicado en el Distrito Metropolitano de Quito - Cárdenas Crespo, Ana Cristina (2016)
This degree work is focused on designing a plan to improve the service quality for BamBao restaurant, located in the Metropolitan District of Quito. In the first chapter the theoretical framework is developed, which contains pertinent and relevant information on the subject to be developed, it will help with the project. The second chapter conducts an analysis of the current situation of the company, where primary data of the establishment is recollected, such as location, mission, vision, business goals, organizational structure, competitive advantage and customer perspective. In chapter three a processes analysis is made or a map of current processes also called blueprint, in which an analysis area are identified, the service processes area described and prepared, critical incidents and possible errors are listed and a SWOT cross analysis is created. In chapter four the proposal and planning improvements arises, by creating goals and quality policies and quality indicators define the organizational restructure and responsibilities are assigned, optimized map processes are performed, strategies and measurement, also analysis and improvement. The proposed intervention is presented, education, training strategies and budget for the project in the chapter five. Finally, conclusions and recommendations are presented in the project.